Comparative characteristics of the transcriptional activity of CDH1, CTNNB1, VEGFA genes and expression of proteins E-cadherin, β-catenin and VEGFA, coded by these genes in metastatic and non-metastatic endometrioid endometrial carcinoma - Tumanskiy, V. A.; Chepets, A. V.; Kamyshnyi, А. М.; Туманський, Валерій Олексійович; Чепець, О. В.; Камишний, Олександр Михайлович; Туманский, В. А.; Чепец, А. В.; Камышный, А. М. (Запорізький державний медичний університет, 2016)
The violation of Wnt-signaling pathway and cyclic neoangiogenesis is early events in endometrial carcinogenesis. In this process an important role is played by epigenetic modiﬁcations and mutations of CDH1, CTNNB1, VEGFA genes, followed by expression violations of E-cadherin, β-catenin, VEGFA encoded by them. The aim. To study the expression levels of mRNA of CDH1, CTNNB1, VEGFA genes and the expression levels of E-cadherin, β-catenin, VEGFA in non-metastatic endometrioid endometrial carcinoma (EEC) and in EEC with metastases to regional lymph nodes. Materials and methods. Immunohistochemical study of invasive рТ1-4N0Mx endometrioid endometrial carcinoma (EEC) (n=56; age – 42–83 years), invasive рТ1-4N1-2Mx EEC (n=30; age – 48–79 years), samples of normal proliferative endometrium (PE) (n=30; age – 41–62 years) was performed. Molecular-genetic study of invasive рТ1-4N0Mx EEC (n=10; age – 45–67 years), invasive рТ1-4N1-2Mx EEC (n=10; age – 44–63 years), samples of PE (n=10; age – 46–59 years) was performed. Results. EEC is characterized by the lower mRNA expression level of CDH1 gene and by the higher mRNA expression levels of CTNNB1, VEGFA genes in comparison with the PE. E-cadherin expression level is 32.6 % lower in non-metastatic EEC and also is 58.10 % lower in metastatic EEC in comparison with the PE. β-catenin expression level is 32.56 % lower in non-metastatic EEC and also is 58.11 % lower in metastatic EEC in comparison with the PE. VEGFA expression level is 27.72 % higher in non-metastatic EEC and also is 17.87 % higher in metastatic EEC in comparison with the PE. There is lower β-catenin expression level in metastatic EEC in comparison with non-metastatic EEC. Non-metastatic and metastatic EEC is characterized by the direct medium connections between the mRNA expression levels of CTNNB1 and VEGFA genes (γ=0.44), between the mRNA expression level of CTNNB1 gene and VEGFA expression level in the tumor (γ=0.37). Conclusions. These changes contribute to tumor growth, invasion and metastasis. У канцерогенезі рака ендометрію ранніми подіями є порушення Wnt-сигнального шляху та циклічного ангіогенезу. Важливу роль при цьому відіграють епігенетичні модифікації генів і мутації генів CDH1, CTNNB1, VEGFА з дальшим порушенням експресії кодованих ними протеїнів – Е-кадгерину, β-катеніну, VEGFА. Мета роботи – вивчити молекулярно-генетичними методами рівень експресії мРНК генів CDH1, CTNNB1, VEGFА, імуногістохімічним методом – рівні експресіі Е-кадгерину, β-катеніну, VEGFA в ендометріоїдній аденокарциномі ендометрію без метастазів і з метастазами в регіонарні лімфовузли. Матеріали та методи. Імуногістохімічним методом вивчена інвазивна рТ1-4N0MхG1-3 ендометріоїдна аденокарцинома ендометрію (ЕАЕ) (n=56; вік – 42–83 роки), інвазивна рТ1-4 N1-2MхG1-3 ЕАЕ (n=30; вік – 48–79 років) і зразки ендометрію фази проліферації (ПЕ) (n=56; вік – 41–62 роки). Молекулярно-генетичним методом вивчена інвазивна рТ1-4N0MхG1-3 ЕАЕ (n=10; вік – 45–67 років), інвазивна рТ1-4N1-2MхG1-3 ЕАЕ (n=10; вік – 44–63 роки) та зразки ПЕ (n=10; вік – 46–59 років). Результати. В ЕАЕ порівняно з нормальним ПЕ знижений рівень експресії мРНК гена CDH1, а також підвищені рівні експресії мРНК генів CTNNB1 і VEGFA. Рівень експресії Е-кадгерину в неметастатичній ЕАЕ знижений на 32,36 %, а в метастатичній ЕАЕ – на 58,10 % порівняно з нормальним ПЕ. Рівень експресії β-катеніну в неметастатичній ЕАЕ знижений на 32,56 %, в метастатичній ЕАЕ – на 58,11 % порівняно з нормальним ПЕ. Рівень експресії VEGFA в неметастатичній ЕАЕ підвищений на 27,72 %, в метастатичній ЕАЕ – на 17,87 % порівняно з нормальним ПЕ. В ЕАЕ з метастазами визначається нижчий рівень експресії β-катеніну в пухлинних клітинах, порівнюючи з інвазивною неметастатичною аденокарциномою. У неметастатичній і метастатичній ЕАЕ спостерігаються прямі помірні зв’язки між рівнями експресії мРНК генів CTNNB1 і VEGFA (γ=0,44), між рівнем експресії мРНК гена CTNNB1 і рівнем експресії судинного ендотеліального фактора росту VEGFA у тканині пухлини (γ=0,37 ). В канцерогенезе рака эндометрия ранними событиями являются нарушение Wnt-сигнального пути и циклического неоангиогенеза. Важную роль при этом играют эпигенетические модификации и мутации генов CDH1, CTNNB1, VEGFА с последующим нарушением экспрессии кодируемых ими протеинов – Е-кадгерина, β-катенина, VEGFА. Цель работы – изучить молекулярно-генетическими методами уровни экспрессии мРНК генов CDH1, CTNNB1, VEGFА, иммуногистохимическим методом – уровни экспрессии Е-кадгерина, β-катенина, VEGFA в эндометриоидной аденокарциноме эндометрия (ЭАЭ) без метастазов и с метастазами в регионарные лимфоузлы. Материалы и методы. Иммуногистохимическим методом изучены инвазивная рТ1-4N0MxG1-3 эндометриоидная аденокарцинома эндометрия (ЭАЭ) (n=56; возраст – 42–83 года), инвазивная рТ1-4N1-2MxG1-3 ЭАЭ (n=30; возраст – 48–79 лет) и образцы эндометрия фазы пролиферации (ПЕ) (n=30; возраст – 41–62 года). Молекулярно-генетическим методом изучены инвазивная рТ1-4N0Mx ЭАЭ (n=10; возраст – 45–67 лет), инвазивная рТ1-4N1-2Mx ЭАЭ (n=10; возраст – 44–63 года) и образцы ПЕ (n=10; возраст – 46–59 лет). Результаты. В ЭАЭ в сравнении с нормальным ПЭ снижен уровень экспрессии мРНК гена CDH1, а также повышены уровни экспрессии мРНК генов CTNNB1 и VEGFA. Уровень экспрессии Е-кадгерина в неметастатической ЭАЭ снижен на 32,36 %, в метастатической ЭАЭ – на 58,10 % в сравнении с нормальным ПЭ. Уровень экспрессии β-катенина в неметастатической ЭАЭ снижен на 32,56 %, в метастатической ЭАЭ – на 58,11 % в сравнении с нормальным ПЭ. Уровень экспрессии VEGFA в неметастатической ЭАЭ повышен на 27,72 %, в метастатической ЭАЭ – на 17,87 % в сравнении с нормальным ПЭ. В ЭАЭ с метастазами определяется более низкий уровень экспрессии β-катенина в опухолевых клетках по сравнению с инвазивной неметастатической аденокарциномой. В неметастатической и метастатической ЭАЭ прослеживаются прямые умеренные связи между уровнями экспрессии мРНК генов CTNNB1 и VEGFA (γ=0,44), между уровнем экспрессии мРНК гена CTNNB1 и уровнем экспрессии сосудистого эндотелиального фактора роста VEGFA в ткани опухоли (γ=0,37). Выводы. Данные изменения способствуют опухолевому росту, инвазии и метастазированию ЭАЭ.
Порівняльна характеристика транскрипційної активності генів CDH1, CTNNB1, VEGFA та експресії кодованих ними білків Е-кадгерину, β-катенінута VEGFA вметастатичній ендометріоїдній аденокарциномі тіла матки і в аденокарциномі без метастазів
Сравнительная характеристика транскрипционной активности генов CDH1, CTNNB1, VEGFA и экспрессии кодируемых ими белков Е-кадгерина, β-катенина и VEGFA в метастатической эндометриоидной аденокарциноме тела матки и в аденокарциноме без метастазов
Keywords: Endometrial Neoplasms; Cadherins; beta Catenin; VEGFA protein; Human; Polymerase Chain Reaction; RNA; Messenger; карцинома ендометрію; Е-кадгерин; β-катенін; CTNNB1; VEGFA; ПЛР; мРНК; карцинома эндометрия; β-катенин; ПЦР; мРНК